(untitled) (Proceedings of Southern Federal University. Philology, 2025)
https://doi.org/10.18522/1995-0640-2025-3-65-75 The article reveals the features of modern translation discourse, its evolution, key trends, and potential for implementation in the context of global changes and challenges. The aim of the study is to identify the characteristics, interconnections, and patterns of translation discourse, which integrates several discursive practices. The research methodology is based on general scientific methods of observation, systematization, and description, and also includes elements of content analysis, contextual and discourse analysis, and comparative analysis. The relevance of the study is linked to the need to identify common and unique forms of expression, as well as formats characteristic of translation discourse. The research material included representative sources reflecting three actively developing discursive practices - sub-discourses of translation discourse: translation studies discourse, translation discourse, and professional discourse of translators. Similarities and differences in the formation and realization of discourse-forming features of these discursive practices, as well as their polydiscursive nature, have been established. The studied discursive practices demonstrate both universal features, such as the translator being the main participant and agent of the discourse regardless of its subtype, and unique characteristics. Each of the analyzed discursive practices shows a stable nature and alignment with current trends in the profession. At the same time, the unique aspects of these practices concern their goals, chronotope, formats, and genres, which shape the thematic focus of each discourse direction. Thus, the study has revealed the dual nature of translation discourse: on one hand, its dynamism, and on the other, its stability in development. A distinctive feature of translation discourse is the continuity and integrative nature of its subtypes - discursive practices - where activities within one practice become the object or subject of another discursive practice. The study has helped define the boundaries of professional institutional translation discourse, thereby contributing to the development of modern integrative translation studies. The prospects for further research lie in the cross-cultural analysis of discourse. Key words: translation discourse, polydiscursivity, sub-discourse, professional discourse, socio-communicative characteristics